A new predictive indicator by arthrography for future acetabular growth following conservative treatment of developmental dysplasia of the hip. Issue 3 (May 2016) - Satsuma, Shinichi; Kobayashi, Daisuke; Kinugasa, Maki; Takeoka, Yoshiki; Kuroda, Ryosuke; Kurosaka, Masahiro
Abstract : The aim of this study was to find a new predictive indicator for acetabular growth of developmental dysplasia of the hip. Seventy-three hips that were diagnosed with developmental dysplasia of the hip and treated by conservative reduction were included in our study. In 30 hips with center-edge angle⩽10° at age 4, the center-edge of the acetabular limbus angle (CEALA) in the arthrogram was measured. On the basis of the results, CEALA was significantly smaller in the secondary acetabular dysplasia group than in the normal group at maturity. In conclusion, CEALA is a more reliable and accurate predictive indicator for acetabular development than center-edge angle or acetabular index.